Modified two-dimensional metal organic framework nanosheet membrane as well as preparation method and separation application thereof

By applying solvent steam treatment to the two-dimensional metal organic framework nanosheet membrane, the interaction force between nanosheets is enhanced, the problem of decreased selectivity of gas separation under high temperature conditions is solved, and high-performance gas separation is achieved.

CN119607910AActive Publication Date: 2025-03-14DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202311175461.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-12
Publication Date
2025-03-14
Estimated Expiration
2043-09-12

AI Technical Summary

Technical Problem

The two-dimensional metal organic skeleton nanosheet membrane has a reduced selectivity for gas separation due to uneven spacing between the slit channels between nanosheets under high temperature conditions.

Method used

The two-dimensional metal organic framework nanosheet membrane is controlledly modified by solvent steam treatment, enhancing the interaction force between adjacent nanosheets and reducing the possibility of macromolecular gas passing through the inter-nanosheet channels.

Benefits of technology

The separation selectivity of the gas separation membrane is improved and the separation performance is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004445351810000011
    Figure HDA0004445351810000011
  • Figure HDA0004445351810000012
    Figure HDA0004445351810000012
  • Figure HDA0004445351810000021
    Figure HDA0004445351810000021
Patent Text Reader

Abstract

The invention discloses a modified two-dimensional metal organic framework nanosheet membrane and a preparation method and gas separation application thereof. The prepared original two-dimensional metal organic framework nanosheet membrane is controllably modified through solvent steam treatment, the interaction force between adjacent nanosheet layers in the nanosheet membrane is enhanced, macromolecular gas is inhibited from passing through channels between the nanosheet layers, and the separation selectivity is improved. The preparation and modification method of the original nanosheet film comprises the following steps: (1) synthesizing a metal organic framework layered precursor by a solvothermal method; (2) stripping the layered precursor of the metal organic framework by combining a wet ball milling method and an ultrasonic dispersion method to obtain a two-dimensional metal organic framework nanosheet; (3) assembling the two-dimensional metal organic framework nanosheet on the surface of the porous carrier to form an original two-dimensional layered metal organic framework nanosheet film; and (4) carrying out modification on the nanosheet film through solvent steam treatment. The modified two-dimensional metal organic framework nanosheet film prepared by the method has excellent gas separation performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of membrane separation and relates to a modified two-dimensional metal organic skeleton nanosheet membrane and a preparation method and separation application thereof. Background Art

[0002] Compared with traditional gas separation technologies such as cryogenic distillation and absorption, gas membrane separation technology does not undergo phase change during the separation process, so it has a series of advantages such as low energy consumption and environmental friendliness, and is currently a research hotspot in the field of gas separation. Metal organic framework materials are a new type of molecular sieve materials, among which two-dimensional metal organic framework materials have great application prospects in the field of gas membrane separation due to their ultra-high pore window density, rich pore structure and pore size, rich surface chemical properties, molecular-level thickness and other characteristics.

[0003] Two-dimensional molecular sieve nanosheet membranes have two types of pores, one is a straight-through pore (Type I pore) formed by the intrinsic oriented pore window structure on the nanosheet, and the other is a tortuous interlayer slit channel (Type II pore) formed by the stacking of nanosheets layer by layer. In the gas separation process, small molecular gases can directly penetrate the membrane through the Type I pores on the nanosheets, while large molecular gases can only penetrate the membrane through the tortuous Type II slit channels. Since two-dimensional metal organic framework nanosheets are generally flexible, this leads to uneven spacing between the slit channels between nanosheet layers. Under high temperature conditions, the nanosheet membrane expands, causing more large molecular gases to diffuse through the membrane through the Type II channels, and the gas separation selectivity decreases significantly. Therefore, it is a difficult problem that needs to be solved in the current field of two-dimensional nanosheet membrane gas separation by effectively enhancing the interaction force between adjacent nanosheet layers and inhibiting large molecular gases from passing through the membrane through the channels between nanosheet layers to improve the separation selectivity. Summary of the invention

[0004] The purpose of the present invention is to provide a modified metal organic framework nanosheet membrane and its preparation method and separation application, and to controllably modify the original metal organic framework nanosheet membrane, and the membrane material prepared by the method has excellent gas separation performance. The present invention controllably modifies the prepared original two-dimensional metal organic framework nanosheet membrane through solvent vapor treatment, enhances the interaction force between adjacent nanosheet layers in the nanosheet membrane, inhibits the passage of macromolecular gases along the channels between nanosheet layers, and improves the separation selectivity.

[0005] A method for preparing a modified two-dimensional metal organic framework nanosheet film, first preparing a two-dimensional layered metal organic framework precursor material, combining wet ball milling and ultrasonic dispersion methods to peel off layers from top to bottom to obtain a two-dimensional metal organic framework nanosheet, assembling into a film and drying, and finally, treating the two-dimensional metal organic framework nanosheet film with solvent vapor. The specific preparation process includes the following steps:

[0006] (1) Solvothermal synthesis of metal organic framework layered precursors: divalent zinc salt, benzimidazole and organic solvent are mixed and reacted at 0-200°C for 24-168h to obtain a two-dimensional layered metal organic framework precursor;

[0007] Among them, the molar ratio of each raw material is Zn 2+ ∶benzimidazole ∶organic solvent=1∶0-1.0∶50-200, and the organic ligand cannot be 0;

[0008] (2) exfoliating the metal organic framework layered precursor by combining wet ball milling and ultrasonic dispersion to obtain two-dimensional metal organic framework nanosheets: mixing the two-dimensional layered metal organic framework precursor obtained in step (1) with an organic solvent, ball milling to obtain two-dimensional layered nanosheets, and then ultrasonically dispersing the two-dimensional layered nanosheets in the organic solvent to obtain a nanosheet dispersion, and allowing to settle for 1-730 days;

[0009] Wherein, the mass concentration of the two-dimensional layered nanosheets in the nanosheet dispersion is 0.001-1%.

[0010] (3) assembling the two-dimensional metal organic framework nanosheets on the surface of the porous carrier into an original two-dimensional layered metal organic framework nanosheet membrane: at room temperature -200°C, coating the nanosheet dispersion obtained in step (2) on the surface of the porous carrier to form a film, and drying to obtain an original two-dimensional metal organic framework nanosheet membrane;

[0011] (4) Modification by treating the nanosheet membrane with solvent vapor: vacuum drying the original two-dimensional metal organic framework nanosheet membrane at 60-200°C for 0-12h, and then treating it with solvent vapor driven by N2 at a flow rate of 5-50ml / min for 1min-24h to obtain a modified two-dimensional metal organic framework nanosheet membrane.

[0012] Based on the above technical solution, preferably, in step (1), the divalent zinc salt is Zn(NO3)2, ZnCl2, etc.

[0013] Based on the above technical solution, preferably, in step (1), the reaction temperature is 80-120° C. and the reaction time is 24-72 h.

[0014] Based on the above technical scheme, preferably, in step (1) and step (2), the organic solvent is anhydrous methanol, anhydrous ethanol, N,N-dimethylformamide, etc.

[0015] Based on the above technical solution, preferably, in step (2), the ball milling conditions are: rotation speed of 30-100 rpm, and ball milling time of 1-24 h.

[0016] Based on the above technical solution, preferably, in step (2), the method used to disperse the two-dimensional layered nanosheets in the organic solvent is ultrasonic dispersion, with ultrasonication for 0-60 min and a power of 300-600 W.

[0017] Based on the above technical solution, preferably, in step (2), the static sedimentation is more than 14 days and less than 365 days.

[0018] Based on the above technical solution, preferably, in step (3), the coating temperature is 60-120°C.

[0019] Based on the above technical scheme, preferably, in step (3), the porous carrier is one of a silica carrier, an α-Al2O3 carrier, a γ-Al2O3 carrier, a TiO2 carrier, an anodized aluminum carrier, and a stainless steel carrier; the pore size of the porous carrier is 5nm to 1μm; the shape of the porous carrier is a sheet structure, a fiber structure or a tubular structure.

[0020] Based on the above technical scheme, preferably, in step (3), the coating method includes dipping-pulling, blade coating, spin coating, spray coating, drop coating, vacuum filtration, interface self-assembly method, Langmuir-Shaefer (LS) method, etc.

[0021] Based on the above technical solution, preferably, in step (3), when preparing the original two-dimensional metal organic framework nanosheet film, the amount of the two-dimensional layered nanosheet dispersion added is 1-50 mL / cm 2 carrier.

[0022] Based on the above technical solution, preferably, in step (3), the drying temperature is 60-200° C. and the drying time is 6-24 h.

[0023] Based on the above technical solution, preferably, in step (4), the vacuum drying temperature is 120-160° C., and the vacuum drying time is 3-6 h.

[0024] Based on the above technical scheme, preferably, in step (4), the solvent includes at least one of ammonia water, ethylenediamine, diethylamine, 1,8-octanediamine, 1,12-dodecanediamine, p-phenylenediamine, 1,4-bis(imidazol-1-yl)butane, molten pyrazine, molten pyrimidine, molten 1,3,5-triazine, molten melamine, molten imidazole, oxazole, molten 2-aminopyrazine, molten 3-aminopyridine, molten 4-aminopyridine, and molten 3-aminopyrimidine.

[0025] Based on the above technical solution, preferably, in step (4), the treatment time is 10 min-6 h.

[0026] The metal organic framework nanosheet material described in the present invention is Zn2(Bim)3. When the solvent vapor is 1,8-octanediamine, the modified metal organic framework nanosheet membrane is M1-Zn2(Bim)3. When the solvent vapor is 1,12-dodecanediamine, the modified metal organic framework nanosheet membrane is M2-Zn2(Bim)3.

[0027] The present invention also relates to two-dimensional metal organic framework nanosheets prepared by the method described above and the modification of the nanosheets.

[0028] The present invention also relates to the application of the modified two-dimensional metal organic framework nanosheet membrane described above in gas separation, especially hydrogen / carbon dioxide separation.

[0029] Since the structure of metal organic framework materials is full of easily modified metal nodes and organic functional groups, various chemical groups can be grafted onto the formed crystals through post-synthesis modification to directionally regulate the framework structure and surface chemical properties. Using double chelate ligand vapor to modify adjacent nanosheets in metal organic framework nanosheet membranes can enhance the interaction between adjacent nanosheet layers and minimize the narrow channels between nanosheet layers that can be used for macromolecular gases to pass through, thereby obtaining high-performance separation membranes.

[0030] Beneficial effects: The present invention firstly synthesizes a layered metal organic framework precursor by solvent thermal, then peels off the layers from top to bottom to obtain a two-dimensional layered nanosheet material, and finally assembles a two-dimensional layered nanosheet membrane on the surface of a porous carrier. By subjecting the nanosheet membrane to solvent vapor treatment, the interaction force between adjacent nanosheet layers is enhanced, and the narrow channels between the nanosheet layers through which macromolecular gases can pass are minimized, thereby obtaining a high-performance separation membrane. Using the preparation method described in the present invention, the two-dimensional metal organic framework nanosheet membrane can be controllably modified to obtain a two-dimensional metal organic framework nanosheet membrane material with excellent performance, which has a good application prospect in the separation field. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] The present invention is attached Figure 6 The widths are:

[0032] Figure 1 This is a scanning electron microscope photograph of the Zn2(Bim)3 material synthesized in Example 1;

[0033] Figure 2 This is a scanning electron microscope photograph of the 1,8-octanediamine-modified M1-Zn2(Bim)3 material synthesized in Example 2.

[0034] Figure 3 This is a scanning electron microscope photograph of the 1,12-dodecanediamine-modified M2-Zn2(Bim)3 material synthesized in Example 3;

[0035] Depend on Figure 1-3 It can be seen that the material has an obvious two-dimensional lamellar structure and the lamellar morphology is not destroyed before and after modification.

[0036] Figure 4 The X-ray diffraction pattern of the Zn2(Bim)3 material synthesized in Example 1;

[0037] Figure 5 The X-ray diffraction pattern of the 1,8-octanediamine-modified M1-Zn2(Bim)3 material synthesized in Example 2;

[0038] Figure 6 The X-ray diffraction pattern of the 1,12-dodecanediamine-modified M2-Zn2(Bim)3 material synthesized in Example 3;

[0039] Depend on Figure 4-6 It can be seen that the crystal form remains intact before and after modification. DETAILED DESCRIPTION

[0040] The present invention will be further described in the following examples, but the present invention is not limited thereto.

[0041] Example 1 Preparation of Zn2(bim)3 Precursor

[0042] Dissolve 2 g zinc nitrate and 0.4 g benzimidazole in 80 ml N, N-dimethylformamide and stir for 20 minutes. Transfer the mixture into a 100 ml reactor, place it in an oven, react at 100 degrees Celsius for 72 hours, take out the reactor and cool it to room temperature. The Zn2Bim3 nanoparticles obtained by centrifugation are repeatedly washed with methanol, and the product is dried in an oven at 60 degrees Celsius overnight. Collect the Zn2(Bim)3 precursor powder.

[0043] Scanning electron microscope images show that the product has a distinct step-like morphology (such as Figure 1 ).

[0044] X-ray diffraction confirmed that the product had a Zn2(Bim)3 structure (such as Figure 4 ), proving that the precursor material was successfully synthesized.

[0045] Example 2 Modification of Zn2(bim)3 Precursor

[0046] The Zn2(bim)3 particles prepared in Example 1 were placed in a reaction furnace, evacuated to 0.1Mpa, and vacuum dried at 120°C for 6h. At 120°C, N2 was passed through 500mL 1,8-octanediamine solvent at a flow rate of 20mL / min into the reaction furnace. After continuous ventilation for 3h, pure N2 was used to purge the residual solvent vapor in the reaction furnace, the heating was turned off, and the reaction furnace was naturally cooled to room temperature. The 1,8-octanediamine-modified M1-Zn2(Bim)3 material was obtained.

[0047] Scanning electron microscope images show that the product still has a clear step-like stratified morphology (such as Figure 2 ).

[0048] X-ray diffraction confirmed that the product had the same characteristic peaks as Zn2(Bim)3 (such as Figure 5 ), proving that the crystal structure of the material has not changed after modification.

[0049] Example 3 Modification of Zn2(bim)3 Precursor

[0050] The Zn2(bim)3 particles prepared in Example 1 were placed in a reaction furnace, evacuated to 0.1Mpa, and vacuum dried at 120°C for 6h. At 120°C, N2 was passed through 500mL 1,12-dodecanediamine solvent at a flow rate of 20mL / min into the reaction furnace. After continuous ventilation for 3h, pure N2 was used to purge the residual solvent vapor in the reaction furnace, the heating was turned off, and the reaction furnace was naturally cooled to room temperature. The 1,12-dodecanediamine-modified M2-Zn2(Bim)3 material was obtained.

[0051] Scanning electron microscope images show that the product still has a clear step-like stratified morphology (such as Figure 3 ).

[0052] X-ray diffraction confirmed that the product had the same characteristic peaks as Zn2(Bim)3 (such as Figure 6 ), proving that the crystal structure of the material has not changed after modification.

[0053] Example 4 Preparation of Ultrathin Two-Dimensional Layered Zn2(bim)3 Nanosheets

[0054] The Zn2(bim)3 particles prepared in Example 1 were dispersed in 100 ml of methanol, sealed in a 150 ml ball milling jar, and ball milled at 60 rpm for 1 hour. The solution was then diluted 1.5 times with the same solvent and subjected to water bath ultrasound at 600 watts for 30 minutes. The Zn2(bim)3 nanosheet dispersion was allowed to stand for two weeks to remove large particles that had not been delaminated.

[0055] Example 5 Preparation of Ultrathin Zn2(bim)3 Nanosheet Supported Film

[0056] The α-Al2O3 porous support was preheated to 100°C on a horizontal heating platform, 10 ml of the nanosheet dispersion obtained in Example 2 was taken, and 10 ml of the dispersion was dripped dropwise onto the surface of the α-alumina support (circular with a radius of 0.9 cm) with a pore size of 70 nm using a syringe until the solvent evaporated completely, i.e., the hot drop coating method. The prepared support film was dried at 100°C for 1 hour and stored in a culture dish at room temperature to obtain an ultrathin nanosheet support film Zn2(bim)3.

[0057] Example 6 Modification of Ultrathin Zn2(bim)3 Nanosheet Supported Membrane

[0058] The ultra-thin Zn2(bim)3 nanosheet support film obtained in Example 5 was placed in a reaction furnace, evacuated to 0.1Mpa, and vacuum dried at 120°C for 6h. At 120°C, N2 was passed through 500mL1,8-octanediamine solvent at a flow rate of 20mL / min into the reaction furnace. After continuous ventilation for 1h, pure N2 was used to purge the residual solvent vapor in the reaction furnace, the heating was turned off, and it was naturally cooled to room temperature. The modified ultra-thin nanosheet support film M1-Zn2(bim)3-a was obtained.

[0059] Example 7 Modification of Ultrathin Zn2(bim)3 Nanosheet Supported Membrane

[0060] The ultra-thin Zn2(bim)3 nanosheet support film obtained in Example 5 was placed in a reaction furnace, evacuated to 0.1Mpa, and vacuum dried at 120°C for 6h. At 120°C, N2 was passed through 500mL 1,8-octanediamine solvent at a flow rate of 20mL / min into the reaction furnace. After continuous ventilation for 3h, pure N2 was used to purge the residual solvent vapor in the reaction furnace, the heating was turned off, and it was naturally cooled to room temperature. The modified ultra-thin nanosheet support film M1-Zn2(bim)3-b was obtained.

[0061] Example 8 Modification of Ultrathin Zn2(bim)3 Nanosheet Support Membrane

[0062] The ultra-thin Zn2(bim)3 nanosheet support film obtained in Example 5 was placed in a reaction furnace, evacuated to 0.1Mpa, and vacuum dried at 120°C for 6h. At 120°C, N2 was passed through 500mL 1,8-octanediamine solvent at a flow rate of 20mL / min into the reaction furnace. After continuous ventilation for 6h, pure N2 was used to purge the residual solvent vapor in the reaction furnace, the heating was turned off, and it was naturally cooled to room temperature. The modified ultra-thin nanosheet support film M1-Zn2(bim)3-c was obtained.

[0063] Example 9 Modification of Ultrathin Zn2(bim)3 Nanosheet Support Membrane

[0064] The ultra-thin Zn2(bim)3 nanosheet support film obtained in Example 5 was placed in a reaction furnace, evacuated to 0.1Mpa, and vacuum dried at 120°C for 6h. At 120°C, N2 was passed through 500mL 1,12-dodecanediamine solvent at a flow rate of 20mL / min into the reaction furnace. After continuous ventilation for 1h, pure N2 was used to purge the residual solvent vapor in the reaction furnace, the heating was turned off, and it was naturally cooled to room temperature. The modified ultra-thin nanosheet support film M2-Zn2(bim)3-a was obtained.

[0065] Example 10 Modification of Ultrathin Zn2(bim)3 Nanosheet Support Membrane

[0066] The ultra-thin Zn2(bim)3 nanosheet support film obtained in Example 5 was placed in a reaction furnace, evacuated to 0.1Mpa, and vacuum dried at 120°C for 6h. At 120°C, N2 was passed through 500mL 1,12-dodecanediamine solvent at a flow rate of 20mL / min into the reaction furnace. After continuous ventilation for 3h, pure N2 was used to purge the residual solvent vapor in the reaction furnace, the heating was turned off, and it was naturally cooled to room temperature. The modified ultra-thin nanosheet support film M2-Zn2(bim)3-b was obtained.

[0067] Example 11 Modification of Ultrathin Zn2(bim)3 Nanosheet Support Membrane

[0068] The ultra-thin Zn2(bim)3 nanosheet support film obtained in Example 5 was placed in a reaction furnace, evacuated to 0.1Mpa, and vacuum dried at 120°C for 6h. At 120°C, N2 was passed through 500mL 1,12-dodecanediamine solvent at a flow rate of 20mL / min into the reaction furnace. After continuous ventilation for 6h, pure N2 was used to purge the residual solvent vapor in the reaction furnace, the heating was turned off, and it was naturally cooled to room temperature. The modified ultra-thin nanosheet support film M2-Zn2(bim)3-c was obtained.

[0069] Example 12

[0070] The three mixed matrix membranes prepared in Examples 5-11 were encapsulated in a Wicke-Kallenbach membrane module and subjected to a hydrogen / carbon dioxide (50:50 ml / min) gas separation test at room temperature and ΔP = 0 bar. (Under standard conditions, 1 GPU = 1×10 -6 cm 3 / cm 2 ·s·cmHg). It can be seen from the data in the table that the mixed matrix membrane material exhibits excellent hydrogen / methane separation performance.

[0071] serial number Steam treatment time <![CDATA[H2 / CO2 separation coefficient]]> <![CDATA[H2 Permeation (GPU)]]> <![CDATA[CO2 Permeation Rate (GPU)]]> <![CDATA[Zn2(bim)3]]> 0 190 938 4.94 <![CDATA[M1-Zn2(bim)3-a]]> 1h 366 961 2.63 <![CDATA[M1-Zn2(bim)3-b]]> 3h 384 863 2.25 <![CDATA[M1-Zn2(bim)3-c]]> 6h 231 906 3.92 <![CDATA[M2-Zn2(bim)3-a]]> 1h 289 1023 3.54 <![CDATA[M2-Zn2(bim)3-b]]> 3h 312 1099 3.52 <![CDATA[M2-Zn2(bim)3-c]]> 6h 347 1042 3.00

Claims

1. A method for preparing a modified two-dimensional metal organic framework nanosheet film, characterized in that: The steps include: (1) mixing a divalent zinc salt, benzimidazole and an organic solvent, and reacting the mixture at 0-200° C. for 24-168 hours to obtain a precursor of a two-dimensional layered metal-organic framework; Among them, the molar ratio of each raw material is Zn 2+ ∶benzimidazole ∶organic solvent=1∶0-1.0∶50-200, and the organic ligand cannot be 0; (2) mixing the precursor of the two-dimensional layered metal organic framework obtained in step (1) with an organic solvent, ball milling to obtain two-dimensional layered nanosheets, and then ultrasonically dispersing the two-dimensional layered nanosheets in the organic solvent to obtain a nanosheet dispersion, and allowing it to settle for 1-730 days; Wherein, the mass concentration of the two-dimensional layered nanosheets in the nanosheet dispersion is 0.001-1%; (3) at room temperature -200°C, coating the nanosheet dispersion obtained in step (2) on the surface of a porous carrier to form a film, and drying to obtain a two-dimensional metal organic framework nanosheet film; (4) The two-dimensional metal organic framework nanosheet membrane is vacuum dried at 60-200° C. for 0-12 h, and then the two-dimensional metal organic framework nanosheet membrane is treated with solvent vapor driven by N2 at a flow rate of 5-50 ml / min for 1 min-24 h to obtain a modified two-dimensional metal organic framework nanosheet membrane.

2. The preparation method according to claim 1, characterized in that: In step (1), the divalent zinc salt is Zn(NO3)2 or ZnCl2.

3. The preparation method according to claim 1, characterized in that: In step (1) and step (2), the organic solvent is anhydrous methanol, anhydrous ethanol or N,N-dimethylformamide.

4. The preparation method according to claim 1, characterized in that: In step (2), the ball milling time is 1-24h and the rotation speed is 30-100rpm.

5. The preparation method according to claim 1, characterized in that: In step (2), the ultrasonic time is 0-60 min and the power is 300-600 W.

6. The preparation method according to claim 1, characterized in that: In step (3), the porous carrier is one of a silicon oxide carrier, an α-Al2O3 carrier, a γ-Al2O3 carrier, a TiO2 carrier, an anodized aluminum carrier, and a stainless steel carrier; the pore size of the porous carrier is 5 nm to 1 μm; the shape of the porous carrier is a sheet structure, a fiber structure, or a tubular structure; The coating method includes at least one of dipping-pulling, scraping, spin coating, spraying, dripping, wiping, vacuum filtration, interface self-assembly method and Langmuir-Shaefer (LS) method.

7. The preparation method according to claim 1, characterized in that: In step (3), the drying temperature is 60-200° C. and the drying time is 6-24 hours.

8. The preparation method according to claim 1, characterized in that: In step (4), the solvent is at least one of ammonia water, ethylenediamine, diethylamine, 1,8-octanediamine, 1,12-dodecanediamine, p-phenylenediamine, 1,4-bis(imidazol-1-yl)butane, molten pyrazine, molten pyrimidine, molten 1,3,5-triazine, molten melamine, molten imidazole, oxazole, molten 2-aminopyrazine, molten 3-aminopyridine, molten pyrrole, molten 2-aminopyrrole, and molten 3-aminopyrrole.

9. A two-dimensional metal organic framework nanosheet film prepared by the method according to any one of claims 1 to 8.

10. Use of the two-dimensional metal organic framework nanosheet membrane described in claim 9 in gas separation.

Citation Information

Patent Citations

  • Modified metal organic framework nano-sheet and preparation method thereof

    CN111282405A

  • Preparation method for synthesizing ZIF-67 membrane through in-hole membrane formation

    CN113019133A

  • Nanoporous thin films and multi-functional layers via spatially organized polymers

    US20080268226A1

  • Grease compositions having polyurea thickeners made with isocyanate terminated prepolymers

    US20200199485A1

  • Metal organic structure nanosheet and production method therefor

    WO2018016650A1